1975
DOI: 10.1172/jci107967
|View full text |Cite
|
Sign up to set email alerts
|

Studies on human plasma C1 inactivator-enzyme interactions. I. Mechanisms of interaction with C1s, plasmin, and trypsin.

Abstract: A B S T R A C T This study has

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
1

Year Published

1976
1976
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(85 citation statements)
references
References 42 publications
(26 reference statements)
4
80
1
Order By: Relevance
“…Cl-inhibitor, a plasma protein with a very high amount of carbohydrates (34% by wt, 17% of which is sialic acid) is composed of a single polypeptide chain ofM r 105 000 [1][2][3][4]. It inhibits a variety of enzymes of the complement system as well as others (e.g., plasmin, kallikrein, Hageman factor).…”
Section: Introduction 2 Materials and Methodsmentioning
confidence: 99%
“…Cl-inhibitor, a plasma protein with a very high amount of carbohydrates (34% by wt, 17% of which is sialic acid) is composed of a single polypeptide chain ofM r 105 000 [1][2][3][4]. It inhibits a variety of enzymes of the complement system as well as others (e.g., plasmin, kallikrein, Hageman factor).…”
Section: Introduction 2 Materials and Methodsmentioning
confidence: 99%
“…Conflicting analytic gel studies have been published concerning the interaction of purified Cl-Inh and Cis. Some studies do show evidence of proteolytic degradation of the inhibitor concomitant to the formation of stable complexes on SDS-PAGE (24,55,57), whereas others do not (23,25,26,53). Moreover, studies that have demonstrated proteolysis of Cl-Inh by Cis disagree whether cleavage is enhanced (24) in the presence of heparin or not (57).…”
Section: Ci-cl-inh and Kallikrein-cl-inh Complexes In Patients Withmentioning
confidence: 99%
“…Cl-Inh is the only known inhibitor in plasma of activated Clr and Cls, components of the classical pathway of complement (18), and the major inhibitor of activated Factor XII (Hageman factor) and kallikrein of the contact pathway of coagulation (19)(20)(21)(22). Inhibition of these so-called target proteinases by functional Cl-Inh comprises both proteolytic cleavage of a substrate-like peptide bond in the reactive center of the inhibitor and covalent linkage of the proteinase to the inhibitor: formation of bimolecular proteinase-C1-Inh complexes (18,20,(22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the esterase activity of plasmin is only slightly inhibited by a.2 macroglobulin (Ganrot, *1967b). The inhibition of plasmin by a2 macroglobulin (Ganrot, 1967b;Miillertz, 1972Miillertz, , 1974, antithrombin III (a2 protein) (Highsmith & Rosenberg, 1974) al anti-trypsin (Hercz, 1974 and Cl-esterase inhibitor (a2 protein) (Harpel & Cooper, 1975 …”
Section: Other Inhibitors In the Crude Preparationmentioning
confidence: 99%